Gramicidin A in Asymmetric Lipid Membranes - Oleg V. Kondrashov; Sergey A. Akimov (Biomolecules)
Gramicidin A is a natural antimicrobial peptide produced by Bacillus brevis. Its transmembrane dimer is a cation-selective ion channel. The channel is characterized by the average lifetime of the conducting state and the monomer–dimer equilibrium constant. Dimer formation is accompanied by deformations of the membrane. We theoretically studied how the asymmetry in lipid membrane monolayers influences the formation of the gramicidin A channel. We calculated how the asymmetry in the spontaneous curvature and/or lateral tension of lipid monolayers changes the channel lifetime and shifts the equilibrium constant of the dimerization/dissociation process. For the asymmetry expected to arise in plasma membranes of mammalian cells upon the addition of gramicidin A or its derivatives to the cell exterior, our model predicts a manifold increase in the average lifetime and equilibrium constant.